The antimicrobial efficacy of elaeis guineensis: characterization, in vitro and in vivo studies - Vijayarathna, S.; Zakaria, Z.; Chen, Y.; Latha, L.Y.; Kanwar, J.R.; Sasidharan, S. (2012)
The urgent need to treat multi-drug resistant pathogenic microorganisms in chronically infected patients has given rise to the development of new antimicrobials from natural resources. We have tested Elaeis guineensis Jacq (Arecaceae) methanol extract against a variety of bacterial, fungal and yeast strains associated with infections. Our studies have demonstrated that E. guineensis exhibits excellent antimicrobial activity in vitro and in vivo against the bacterial and fungal strains tested. A marked inhibitory effect of the E. guineensis extracts was observed against C. albicans whereby E. guineensis extract at 1/2, 1, or 2 times the MIC significantly inhibited C. albicans growth with a noticeable drop in optical density (OD) of the bacterial culture. This finding confirmed the anticandidal activity of the extract on C. albicans. Imaging using scanning (SEM) and transmission (TEM) electron microscopy was done to determine the major alterations in the microstructure of the extract-treated C. albicans. The main abnormalities noted via SEM and TEM studies were the alteration in morphology of the yeast cells. In vivo antimicrobial activity was studied in mice that had been inoculated with C. albicans and exhibited good anticandidal activity. The authors conclude that the extract may be used as a candidate for the development of anticandidal agent.